PENGARUH GREEN ACCOUNTING, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KINERJA KEUANGAN - Syafitri, Anatasya Nur; Riftiasari, Dinar (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This study intends to evaluate the effect of Green Accounting, Company Size, and Leverage on Financial Performance. Companies engaged in manufacturing have an important role in the Indonesian economy and are one of the largest contributors to non-oil and gas GDP. The population in this study is from manufacturing companies engaged in food and beverages listed on the IDX for the 2019-2023 period. Green accounting focuses on environmental costs, company size uses the natural lagorithm of total assets and leverage using DER, while financial performance uses ROA. The research method applied is quantitative. The sampling procedure is “purposive sampling”, which is the selection of ten companies based on predetermined criteria. The analysis methods used in this study include descriptive statistical tests, classical assumption tests, and multiple linear regression. This study uses secondary data sourced from financial statements. The results show green accounting affects the company's financial performance with a significant value of 0.012 and a regression coefficient of -88.769, company size does not affect the company's financial performance with a significant value of 0.471 and a regression coefficient of 0.378, and leverage has an influence on the company's financial performance with a significant value of 0.034 and a regression coefficient of -4.273. Green accounting, company size, and leverage simultaneously affect the company's financial performance with a significant value of 0.001.